Effect of nanoparticles in drilling fluids on the transportation of different cutting sizes in a rotating horizontal pipe - Oseh, Jeffrey O.; M.N.A.M., Norddin; Duru, Ugochukwu I.; Ngouangna, Eugene N.; Issham, Ismail; Gbadamosi, Afeez Olayinka; Agi, Augustine Aja; Yahya, Muftahu N.; Okoli, Nnanna; Abuhoureyah, Rafeq A. (Sultan Qaboos University, 2024)
Cutting transport is difficult in horizontal borehole regions due to the limited axial velocity distribution. This causes transported cuttings to gravitate to the bottom, generating cutting beds and leading to drilling mishaps. Water-based mud (WBM) that includes nanoparticles (NPs) to determine the cutting transport ratio (CTR) performance using copper II oxide (CuO), aluminium oxide (Al2O3), magnesium oxide (MgO), and silicon dioxide (SiO2) in a horizontal borehole needs further investigation. These NPs ability to transport 0.80–3.60 mm cutting sizes was tested using concentrations of 1.0 and 2.0 g circulated through a horizontal annulus at 3.5 m/s and 120 rpm. With 2.0 g, MgO lowered the viscosity by 60%, whereas SiO2, CuO, and Al2O3 increased it by 49%, 10%, and 87%, respectively. CuO NP decreased the fluid loss (FLAPI) the best, followed by MgO, SiO2, and Al2O3. The FLAPI of the WBM, which was 9.4 mL, dropped to 4.8, 5.1, 7.4, and 8.2 mL with CuO, MgO, SiO2, and Al2O3 NPs, respectively. The CTR performance of the NPs increased with concentration and decreased with increasing cutting size. CuO, having less viscosity than Al2O3 and SiO2, carried the most cutting at all concentrations and sizes. It increased the CTR by 28.8–31.1%, whereas Al2O3 and SiO2 increased it by 22.7–26.7% and 16.7–22.2%, respectively. The lowest increase was 13.6–17.8% for MgO NP. This study demonstrates the favourable impact of NP concentrations on the performance of drilling fluids while presenting many choices for the selection of NPs.